Efficacy and safety of adalimumab biosimilar (HS016) in inflammatory bowel disease from the real-world study - Wang, Fang; Li, Xiaofei; Shi, Yanting; Zhou, He; Yang, Gang; Li, Ruixia; Wu, Tong; Liang, Jie (Frontiers in Pharmacology, 2023)
Objective: Adalimumab (ADA) is an effective treatment for inflammatory bowel disease (IBD), both ulcerative colitis (UC) and Crohn's disease (CD). The equal effect between the original ADA and biosimilars from Europe and the United States has been shown. However, the biosimilar of ADA is different in China. The effectiveness and safety data of ADA biosimilar (HS016) in China have yet to be discovered. Patients and methods: 91 patients (75 CD, 16 UC) received HS016 treatment and were enrolled in this study. Therapeutic response and safety profiles were analyzed. Therapeutic drug monitoring (TDM) was also carried out among nonresponse patients. After being considered as “nonresponse” (after three or six months of treatment), 20 patients’ serum TNFα concentrations were measured and correlated to their disease severity. Results: Among active CD patients (n = 61), 75.4% (46/61) at 12w, 73.8% (45/61) at 26w, 50.8% (31/61) at 52w achieved the clinical response, respectively; 55.7% (34/61) at 12w, 65.6% (40/61) at 26w, and 45.9% (28/61) at 52w achieved clinical remission. The maintained remission rates of CD (n = 14) in clinical remission were 100% (14/14) at 12w, 78.6% (11/14) at 26w, and 63.6% (7/11) at 52w, respectively. Among active UC patients, 37.5% (6/16) at 12w and 50% (8/16) at 26w achieved clinical response. Total adverse event rates were 5.5% (5/91) during 52-week visits. Due to the inadequate serum drug concentration, 30.4% (7/23) of patients had poor clinical responses. Elevations of serum anti-drug antibodies occurred in one additional patient (4.3%). Conclusion: ADA biosimilar HS016 had good efficacy and safety in Chinese IBD patients.